The The Use of Google Classroom as an English Learning Media - Yulia Isratul Aini (English Education Study Program Faculty of Teacher Training and Education, 2018)
ABSTRACT: The objective of this writing was to describe the usage of Google Classroom as an English Leraning Media focused on the description of Google Classroom using as the English learning media. The method used in writing this article was literature based by collecting data and information of the topic Google Classroom as e n English learning media. This writing indicated that Googe classroom was very potential to be developed as an English learning media used in virtual class of teaching and learning forum on ICT based. In summary, English teacher can use the Google Classroom as an alternative for teaching and learning media.